Are We Culturally Corrupt? Revisiting the Relationship between Cultural Dimensions And Corruption Perception Index - Indra Soeharto; Nugroho Nugroho (Asia Pacific Fraud Journal, 2017)
ABSTRACTThis research aims to revisit the relationship between two cultural dimensions index (masculinity and power distance) and corruption – as indicated in the Corruption Perception Index (CPI). Two hypotheses were proposed: An increase in the masculinity index increases corruption and an increase in the power distance index increases corruption. Using the latest CPI data from 2012 to 2016 of 67 countries, this research found that the increase in masculinity does not significantly increase corruption. Meanwhile, it is noticed that the increase in power distance significantly increases corruption. Better understanding on such relationship will provide valuable input on how cultural approach is important to fine tune the design of corruption eradication strategy, particularly in Indonesia.At the end, proper strategy will contribute the improvement of Indonesia’s CPI, which will eventually improving Indonesia’s business environment for the investo